Correlation between cardiac index(CI) and cardio ankle vascular index(CAVI) at different degrees of head up tilt table - Akeel Zwain; Ahlam Abood (مجلة الكوفة الطبية, 2013)
Background: Cardio Ankle Vascular Index (CAVI), a new index for arterial stiffness that can be measured by VaSera VS-1000 CAVI device. This is a new method for estimating the level of arteriosclerosis, which is relatively uninfluenced by changes of blood pressure. An association between some arterial fitness indices and cardiac function has been recently demonstrated. CI: is Cardiodynamic measure based on the Cardiac output (CO)which is normalized according to body size ,this is gained by dividing CO on body surface area. Aim: To establish if any significant interrelationship exists between indexed cardiac output (CI) and Cardio ankle vascular Index (CAVI). Further, to introduce a new index as a haemodynemic parameter, notably CI/CAVI. . Method: This study was carried out at Dr.Akeel Zwain private clinic, on 20 healthy male volunteers of a mean age of 30±5 year and BMI of 23.1±1.1 Kg/m². Measurement of cardiac output (CO) is accomplished by estimation of aortic diameter (D) and calculating the velocity time integral (VTI) of aortic flow by Doppler echocardiography, then utilizing the equation: CO=(VTI*D2 *0.785)*heart rate. Measurement of arterial stiffness index (CAVI) can be generated by VaSeraVS-1000 device. A motorized tilting table of incremental degrees; at 0º, 30º and 60º of head up tilt (HUT), was used to bring about peripheral sympathetic outflow modifications, together with postural changes in stroke volume, hence CO and CI. Results: This study demonstrated that there was a statistical significant negative correlation between CI and the degree of head up tilt. CI is significantly decreased relative to increase of HUT degree, in a stepwise manner; CI is significantly lower at 30 and 60 degrees than that at zero degree, (Pearson's correlation coefficient: r=0.63 for 0ºand 30º; r=0.81 for 0ºand 60º, p<0.001 for both; r= 0.71for 30ºand 60º; p<0.05 ). On the other hand, CAVI showed a statistical significant positive correlation relative to the degree of HUT. CAVI was significantly increased, in a stepwise fashion, at 30 and 60 degrees, than that at supine zero degree (Pearson's correlation coefficient: r =0.88 for 0º and 30º; r=0.83 for 0ºand 60º; r=0.81 for 30º and 60º ; p<0.001 for all). Correlation between CI and CAVI at different degrees of HUT was studied, the results demonstrated a significant negative correlation exists between CI and CAVI (r = - 0.47; p<0.05). The result of dividing the two indexes, by each other, CI/CAVI, yielded significant inverse inter relationship with respect to degree of HUT; being lower at 30ºand 60º than that obtained at 0ºtilt. It was significantly lower, in a slope wise pattern, at 60º than that at 30º of tilt (r =0.65 for 0º and 30º; r =0.78, for 0º and 60º; r =0.68, for 30º and 60º; p<0.001 for all). Conclusion: the present investigation reveals an inverse interrelationship between CI and CAVI; a decrease of CI is consistently associated with an increase of CAVI. A new index CI/CAVI may be proposed; it can be employed to early detect subclinical atherosclerosis impact on cardiac muscle pump function. This new integrated parameter could possibly serve for fitness assessment, and for cardiovascular risk stratification. Abbreviations: CAVI, cardio ankle vascular index; HUT: head up tilt; CI: cardiac index; CO: cardiac output; VTI: velocity time integral ; D: aortic diameter; SV ,stroke volume; HR, heart rate; Dd :change of diameter ; PS, systolic pressure ; Pd, diastolic pressure